Photochemical Hydroxyl Group Abstraction from N-Hydroxypyridine-2(1H)-thione Isolated in a Solid Hydrogen Matrix: Photogeneration of 2-Mercaptopyridine - Hanna Rostkowska; Maciej J. Nowak; Igor Reva; Leszek Lapinski (Molecules)
Monomers of N-hydroxypyridine-2(1H)-thione were isolated in low-temperature matrices of solid normal hydrogen (n-H2). The matrix-isolated compound was irradiated with UV-B (λ = 305 nm) or UV-A (λ > 360 nm) light. Upon such irradiation, the initial form of N-hydroxypyridine-2(1H)-thione was completely consumed and converted into photoproducts. 2-Mercaptopyridine and water were identified as the main products of these photochemical transformations. Identification of photoproduced 2-mercaptopyridine is unquestionable. It is based on the identity of two sets of IR bands: (i) the bands observed in the IR spectrum recorded (in a separate experiment) for monomers of 2-mercaptopyridine trapped in an n-H2 matrix and (ii) a set of IR bands observed in the spectrum recorded after UV irradiation of N-hydroxypyridine-2(1H)-thione. It should be emphasized that the UV-induced processes, occurring for N-hydroxypyridine-2(1H)-thione isolated in an n-H2 matrix, lead to products that are significantly different from those generated from the compound trapped in solid Ar or in solid N2.